MISTIS PERIUK TUMBUH DI DESA SUBO KECAMATAN ALOR SELATAN, KABUPATEN ALOR - Tabita Asmiyanti Serangkai; Tersia Lengmalu; Petrus Mau Telu Dony (Adiba Aisha Amira, 2026)
Tumbuh is a natural phenomenon believed to have mystical and sacred value by the people of Subo Village, South Alor District. This phenomenon takes the form of a clay pot (periuk) believed to “grow” or increase naturally without human intervention. The existence of Periuk Tumbuh is not only seen as a natural wonder but also as a cultural heritage of the ancestors rich in spiritual, social, and local wisdom values. The local community believes that Periuk Tumbuh has a close relationship with ancestral spirits and natural forces that maintain the balance of human life and the environment. Therefore, its existence is highly respected and protected through various taboos, traditional rituals, and oral traditions passed down through generations. The research method used is a qualitative method with an ethnographic approach, through observation techniques, in-depth interviews with traditional leaders, community leaders, and local residents, as well as documentation. The results show that Periuk Tumbuh not only serves as a symbol of natural wonder but also as a medium for community unity, strengthening cultural identity, and a means of moral education, such as respect for nature, belief in ancestors, and the importance of maintaining harmony between humans and the environment. Thus, Periuk Tumbuh plays an important role in maintaining local cultural sustainability and enriching Indonesia’s cultural heritage, especially in South Alor.